2019
DOI: 10.18273/revfue.v17n2-2019007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the concentrations of xanthan gum, hydroxypropyl starch and potassium chloride on the flow properties of drilling fluid formulations

Abstract: Drilling operation of oil wells involves high costs and risks. With recent discoveries of deeper reservoirs and difficult to access, there was an increase in the number of horizontal wells drilled and far-reaching, and, thereat, new challenges with operational problems. Fluids, or muds, drilling are essential to the well drilling process, confirming the need to study and find physical, rheological, and filtration properties, appropriate to the complexities in each section and the drilling stage. Optimized form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…12 Another assessment of the most used polymer, xanthan gum (XG), by Alves et al ( 2019) on the XG influence on flow properties of a water-based drilling fluid shows XG increasing content (0.15% to 0.55%) rise in the plastic viscosity and yield point by 28% and 40%, respectfully. 13 Such observations about fluid loss control and rheological improvement by several research studies 14−18 have increased the global drilling polymer industry, which is currently reporting a global market forecast of USD 2,705.4 million by 2030. 19 Many studies have also confirmed that polymers provide thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Another assessment of the most used polymer, xanthan gum (XG), by Alves et al ( 2019) on the XG influence on flow properties of a water-based drilling fluid shows XG increasing content (0.15% to 0.55%) rise in the plastic viscosity and yield point by 28% and 40%, respectfully. 13 Such observations about fluid loss control and rheological improvement by several research studies 14−18 have increased the global drilling polymer industry, which is currently reporting a global market forecast of USD 2,705.4 million by 2030. 19 Many studies have also confirmed that polymers provide thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al (2018), evaluating the potential of aqueous polymers to improve the swelling mechanism of hydrophilic bentonite particles, observed that the addition of engineered synthetic polymers to traditional WBM increased the mud rheology by 14% and reduced fluid loss by 25% . Another assessment of the most used polymer, xanthan gum (XG), by Alves et al (2019) on the XG influence on flow properties of a water-based drilling fluid shows XG increasing content (0.15% to 0.55%) rise in the plastic viscosity and yield point by 28% and 40%, respectfully . Such observations about fluid loss control and rheological improvement by several research studies have increased the global drilling polymer industry, which is currently reporting a global market forecast of USD 2,705.4 million by 2030…”
Section: Introductionmentioning
confidence: 99%
“…To run the oil and gas industry, different expertise areas are involved. , For example, studies related to drilling, completion, hydraulic fracturing, , enhanced oil recovery, , acidizing, organic deposition inhibition, inorganic deposition inhibition, , and the demulsification process are relevant to optimize the oil production. Nevertheless, the quality of water that is discarded or reinjected plays an important role not only in the oil business as a whole but also in the issues related to environmental aspects. Moreover, the treatment of oil-spilled seawater is a challenge around the world, adding motivation to the research on oil–water separation. …”
Section: Introductionmentioning
confidence: 99%